MONITORING OF THE HEAT TRANSFER IN BUILDINGS - Lipnik, Gorazd; Matko, Vojko (International Journal of Computing, 2002)
In paper is introduced measurement method for monitoring of temperatures on big objects. Measurement equipment used in method and results on known object are also introduced. When temperatures are monitored for a long period of time (at least 14 days), the lost of heat, quality of isolation and quality of heat regulation can be estimated.